A 3D-printed Prototype of a Miniaturized Top-Metalized Rectangular Dielectric Resonator Antenna - Sofokleous, Paris; Herraiz Martínez, Francisco Javier; Paz, Eva; Márquez-Segura, Enrique; Padilla, Pablo; Pérez-Escribano, Mario (URSI, 2024)
This paper presents a 3D-printed prototype of a novel top-metalized Dielectric Resonator Antenna (DRA). The inclusion of top metallization induces a modification in the boundary conditions, resulting in a frequency reduction in the fundamental mode of the DRA. Still, it does not degrade its radiation performance. The dielectric part is manufactured using fused deposition modeling (FDM) printing techniques and a commercially available Zirconia-loaded filament. The prototype presents a –10-dB bandwidth from 2.54 to 2.68 GHz with a minimum of –21 dB at 2.60 GHz. The radiation maxima occur in the top and bottom directions, with a simulated gain of 2.7 dBi. Thus, a low-cost and fast method to implement and manufacture a miniaturized DRA is presented.
Keywords: Antenas; Antena